Promotional and Extension Programmes for transforming Indian Agriculture - Kumar, Yogendra; Singh, Tarunendu; Singh, A P; Tiwari, K N (Indian Farming, 2017)
IFFCO’s promotional and extension programmes are systematically organized with the major thrust on improving soil health, promoting balanced and integrated use of nutrient resources to improve N:P:K consumption ratio apart from promoting use of secondary and micronutrients, to create greater awareness among farmers about improved farm technologies through farmers training programmes, group discussions, crop seminars, on farm demonstrations, field days, crop harvest days, T & V programme etc. so as to enrich farmers knowledge and support them to boost crop productivity, produce quality and income through holistic approach of balanced and efficient use of fertilizers, water and other inputs and adoption of best management practices to ensure sustainable high yeild agriculture.